(untitled) (Medical Forum Monthly, 2024)
Objective: To study the histomorphological spectrum of breast diseases at a tertiary care hospital of Lahore. Study Design: Descriptive Study Place and Duration of Study: This study was conducted at the Shalimar Institute of Health Sciences, Lahore from August 2012 to August 2017. Materials and Methods: Five hundred and fifty nine breast specimens sent for histopathology at Shalamar Hospital Laboratory over a span of five years were studied. The specimens include mastectomies, lumpectomies, incisional biopsies and core biopsies. The specimens are then fixed in 10% buffered formalin and paraffin sections are made and stained with Hematoxyline and Eosin for evaluation of histopathological changes. Results: Among 559 cases of breast masses, (age range 10-76 yr.), benign cases comprised of 413 cases (73.88%) and malignant lesion comprised of 146 cases (26.11%).Among the benign lesions Fibroadenoma was the most common benign breast disease (BBD) comprising of 223 cases (39.89 %). Fibrocystic disease was the second most common BBD 34 cases (6.08 %) and breast mastitis was third most common accounting for 26 cases (4.6%).Among the malignant lesions breast carcinoma was the most common lesion accounting for 146 cases (26.11%). The most common type of carcinoma was infiltrating ductal carcinoma NOS 124 cases (22.18%) and second most common was infiltrating lobular carcinoma comprised of 10 cases (1.7%). Conclusion: The most commonly presenting breast disease in our locality is fibroadenoma and it is two times more common than carcinoma. Breast carcinoma is second most common disease and it is a growing health problem among Pakistani females.